Pengaruh Independensi, Pengetahuan Audit Dan Akuntabilitas Audit Terhadap Kualitas Audit - Resya Aulia; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2020)
This research aims to know and test effect of independency, audit knowledge and accountability to audit quality (empirical study on West Sumatera Provincial inspectorate. This research is quantitative research. The population is APIP who work on West Sumatera Provincial inspectorate. The sample of this research includes 40 internal auditors. The data source is primer data. Data was collected by distributing questionnaire to the West Sumatera Provincial inspectorate. The method of data analysis is multiple regression to examine hypothesis 1, 2 and 3. The result of this research show that: (1) independency do not have a significant impact on audit quality, where t hitung < t tabel is 0,688 < 1,685 or sig 0,496 > 0,05, so hypothesis 1 is not accepted. (2) Audit knowledge do not have a significant impact on audit quality, where t hitung < t tabel is 0,515<1,685 or sig 0,610>0,05, so hypothesis 2 is not accepted. (3) Accountability do not have a significant impact on audit quality, where t hitung < t tabel yaitu 0,563 < 1,685 or sig 0,577 > 0,05, so hypothesis 3 is not accepted.